2013
DOI: 10.7202/1016064ar
|View full text |Cite
|
Sign up to set email alerts
|

Traitement des effluents d’abattoir de viande rouge par électrocoagulation-flottation avec des électrodes en fer

Abstract: L’effluent de l’abattoir municipal de la ville de Meknès est caractérisé par une forte charge organique polluante et une coloration rouge due à la concentration élevée en sang. Les analyses physicochimiques et microbiologiques ont révélé des concentrations importantes en paramètres globaux de pollution, et une charge microbiologique marquée par la dominance des coliformes. La demande chimique en oxygène (DCO) moyenne est de 2 240 mg d’O2•L‑1. La concentration moyenne en azote total est de 290 mg•L‑1. Les ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Kabuk et al (2014) applied electrocoagulation in the Leachate treatment and obtained a removal efficiency of TKN removal efficiency of 32%. Khennoussi et al (2013), in the same paper cited above, obtained a removal of 76.2% of total nitrogen.…”
Section: Efficiency Of Removalmentioning
confidence: 66%
See 1 more Smart Citation
“…Kabuk et al (2014) applied electrocoagulation in the Leachate treatment and obtained a removal efficiency of TKN removal efficiency of 32%. Khennoussi et al (2013), in the same paper cited above, obtained a removal of 76.2% of total nitrogen.…”
Section: Efficiency Of Removalmentioning
confidence: 66%
“…While studying phosphorus removal and turbidity of pork effluent with aluminum electrodes, HRT of 80 min and current density of 50 mA cm -2 , Mores et al (2016) obtained a removal of 93.6% of total phosphorus. Khennoussi et al (2013), when treating wastewater from a slaughterhouse and packing plant with electrocoagulation, applying a voltage of 12 V, 25 min contact time and iron electrodes, obtained a removal of 95.4% orthophosphate.…”
Section: Efficiency Of Removalmentioning
confidence: 99%
“…These waters have COD and BOD in order 2827, 1620 mg O 2 /L, respectively[52]. This is confirmed by[53] [54]. Study of Cuetos et al[49] was showed that the first 10 days, nitrogen compounds are degraded and ammonia nitrogen is released into the environment.…”
mentioning
confidence: 70%
“…The natural flotation leads to reduce the turbidity of the OMW by 37.7%, 19.4%, 14.3%, 0.8% and 6% for samples 1, 2, 3, 4 and 5, respectively (Figure 1). Indeed, flotation is a technique used to separate solid or liquid particles from a liquid phase and which consists of bringing on the surface the materials whose density is lower, equal or very slightly higher than that of the base liquid (Khennoussi et al, 2013). Oil may be present as an undispersed surface that usually floats at the interface.…”
Section: Resultsmentioning
confidence: 99%